Association of Low-Attenuation Plaque with Impaired Glucose Tolerance and Type 2 Diabetes Mellitus in Patients with Suspected Coronary Artery Disease - Thomas R. Andersen; Katrine S. Overgaard; Laurits Juhl Heinsen; Roda Abdulkadir Mohamed; Helle Precht; Jess Lambrechtsen; Søren Auscher; Kenneth Egstrup (Biomedicines)
Aim: The aim of this study was to evaluate the differences in plaque composition and burden between normal glycemic status (NGS) and dysglycemia expressed as impaired glucose tolerance (IGT) and type 2 diabetes mellitus (T2DM). Methods: Clinically indicated coronary computed tomography angiography was used to evaluate patients with suspected coronary artery disease (CAD). An oral glucose tolerance test was performed to assess glycemic status. Patients were stratified as NGS, IGT, and T2DM. Plaque volumes were quantified using validated software, with further compositional measurements of low-attenuation, non-calcified, and calcified plaque burden. Results: Of 355 patients with suspected CAD, 220 had NGS, 92 were diagnosed with IGT, and 43 with known T2DM. Low-attenuation plaque volume was significantly higher in IGT (209 mm3, p < 0.02) and T2DM (243 mm3, p = 0.005) compared with NGS (166 mm3). Total plaque burden was similar between all groups, but a significantly greater low-attenuation plaque burden was seen in IGT (p = 0.03) and T2DM (p = 0.02) compared with NGS. The multivariate linear regression model adjusted for clinical risk factors showed that patients with IGT had a greater low-attenuation plaque burden compared with those with NGS (p = 0.03). Interestingly, no significant differences in plaque burdens were observed between those with IGT and T2DM in both univariate and multivariate analyses. Conclusions: Dysglycemia, including impaired glucose tolerance and type 2 diabetes mellitus, was associated with increased low-attenuation plaque burden compared with normal glycemic status. Patients with IGT demonstrated plaque burden similar to patients with known T2DM, underscoring the need for early metabolic intervention.